Cutaneous histoplasmosis as a complication after anti-TNF use - Case report - Gabrielle Aline Zattar; Fernanda Cardoso; Sadamitsu Nakandakari; Cleverson Teixeira Soares (Sociedade Brasileira de Dermatologia, 2015)
AbstractAnti-TNF agents are effective in the treatment of psoriasis. However, they render individuals more susceptible to infections. We report an atypical case of histoplasmosis in an immunosuppressed patient due to anti- TNF therapy. A patient who used anti-TNF for the treatment of psoriasis had had a lesion on the right eyebrow since discontinuation of the medication. The diagnostic hypothesis was basal cell carcinoma, but the histopathological examination was compatible with histoplasmosis.